Targeting Mycobacterium tuberculosis Tumor Necrosis Factor Alpha-Downregulating Genes for the Development of Antituberculous Vaccines - Aaron Olsen (American Society for Microbiology, 2016)
ABSTRACT Tumor necrosis factor alpha (TNF) plays a critical role in the control of Mycobacterium tuberculosis, in part by augmenting T cell responses through promoting macrophage phagolysosomal fusion (thereby optimizing CD4+ T cell immunity by enhancing antigen presentation) and apoptosis (a process that can lead to cross-priming of CD8+ T cells). M. tuberculosis can evade antituberculosis (anti-TB) immunity by inhibiting host cell TNF production via expression of specific mycobacterial components. We hypothesized that M. tuberculosis mutants with an increased capacity to induce host cell TNF production (TNF-enhancing mutants) and thus with enhanced immunogenicity can be useful for vaccine development. To identify mycobacterial genes that regulate host cell TNF production, we used a TNF reporter macrophage clone to screen an H37Rv M. tuberculosis cosmid library constructed in M. smegmatis. The screen has identified a set of TNF-downregulating mycobacterial genes that, when deleted in H37Rv, generate TNF-enhancing mutants. Analysis of mutants disrupted for a subset of TNF-downregulating genes, annotated to code for triacylglycerol synthases and fatty acyl-coenzyme A (acyl-CoA) synthetase, enzymes that concern lipid biosynthesis and metabolism, has revealed that these strains can promote macrophage phagolysosomal fusion and apoptosis better than wild-type (WT) bacilli. Immunization of mice with the TNF-enhancing M. tuberculosis mutants elicits CD4+ and CD8+ T cell responses that are superior to those engendered by WT H37Rv. The results suggest that TNF-upregulating M. tuberculosis genes can be targeted to enhance the immunogenicity of mycobacterial strains that can serve as the substrates for the development of novel anti-TB vaccines. IMPORTANCE One way to control tuberculosis (TB), which remains a major global public health burden, is by immunization with an effective vaccine. The efficacy of Mycobacterium bovis BCG, the only currently approved TB vaccine, is inconsistent. Tumor necrosis factor alpha (TNF) is a cytokine that plays an important role in controlling TB. M. tuberculosis, the causative agent of TB, can counter this TNF-based defense by decreasing host cell TNF production. This study identified M. tuberculosis genes that can mediate inhibition of TNF production by macrophage (an immune cell critical to the control of TB). We have knocked out a number of these genes to generate M. tuberculosis mutants that can enhance macrophage TNF production. Immunization with these mutants in mice triggered a T cell response stronger than that elicited by the parental bacillus. Since T cell immunity is pivotal in controlling M. tuberculosis, the TNF-enhancing mutants can be used to develop novel TB vaccines.